Sage essential oil improves the effectiveness of aloe vera gel on postharvest quality of tomato fruit - Tzortzakis, Nikos G.; Xylia, Panayiota; Chrysargyris, Antonios (My University, 2019)
Edible coating is extensively applied for fresh produce preservation. In the present study, Aloe vera gel (AV) alone or combined with sage essential oil (EO; 0.1% or 0.5%) was used as fruit edible coating in tomatoes. Following treatments, tomatoes were stored at 11 °C and 90% relative humidity (RH) up to 14 days and analyzed for quality maintenance compared with uncoated fruits (control). Results showed that both AV and EO decreased decay symptoms with more pronounced effects on low EO concentration (i.e., 0.1%). The application of 10% of AV coating decreased fruit ethylene emission while EO (0.1% and 0.5%) application increased ethylene emission and respiration rates. AV coating decreased acidity, β-carotene, lycopene content and maintained fruit firmness. High levels of EO (0.5%) increased weight loss but decreased fruits' redness, chroma, total soluble solids, acidity, β-carotene and lycopene content. Total phenolic content and antioxidants maintained or increased during storage when treated with AV and/or EO. Low levels of EO (0.1%) maintained or improved fruit quality characteristics during storage, and this was mirrored by the sensory evaluation preference (including the AV application) and quality related attributes.
Keywords: Aloe vera; Edible coating; Preservation; Quality-related attributes; Sage oil; Tomato